Ex Vivo Magnetic Resonance Imaging of Transplanted Hepatocytes in a Rat Model of Acute Liver Failure. Issue 3 (April 2014) - Puppi, Juliana; Modo, Michel; Dhawan, Anil; Lehec, Sharon C.; Mitry, Ragai R.; Hughes, Robin D.
Hepatocyte transplantation is being evaluated as an alternative to liver transplantation. However, the fate of hepatocytes after transplantation is not well defined. The aims of the study were to improve hepatocyte labeling in vitro using superparamagnetic iron oxide nanoparticles (SPIOs) and to perform in vivo experiments on tracking labeled cells by magnetic resonance imaging (MRI). Human and rat hepatocytes were labeled in vitro for 16 h with clinically approved SPIOs (12.5 μg Fe/ml) and protamine sulfate (3 μg/ml) as a transfection agent. Increased cellular iron uptake was obtained, and cell viability and function were shown not to be affected by labeling. Labeled cells (2, 000/μl) could be detected on T2 -weighted images in vitro using a 7T MR scanner. In a rat model of acute liver failure (ALF), female recipients received intrasplenic transplantation of 2 × 10 7 male rat hepatocytes 28–30 h after intraperitoneal injection of d-galactosamine (1.2 g/kg). There were four groups ( n = 4 each): vehicle injection, injection of freshly isolated cells labeled with CM-DiI, injection of cultured cells labeled with CM-DiI, and injection of cultured cells labeled with both SPIOs and CM-DiI. Ex vivo T2 *-weighted gradientecho images at 7T MRI were acquired at day 7 post-ALF induction. Six days after transplantation, SPIOs were detected in the rat liver as a decrease in the MRI signal intensity in the surviving animals. Histologically, most of the SPIOs were located in Kupffer cells, indicating clearance of labeled hepatocytes. Furthermore, labeled cells could not be detected in the liver by the fluorescent dye or by PCR for the Y-chromosome ( Sry-2 gene). In conclusion, optimum conditions to label human hepatocytes with SPIOs were established and did not affect cell viability or metabolic function and were sufficient for in vitro MRI detection. However, the clearance of hepatocytes after transplantation limits the value of MRI for assessing long-term hepatocyte engraftment.